Putative alternative trans-splicing of leukocyte adhesion-GPCR pre-mRNAs generates functional chimeric receptors. - Chiu, P; Ng, B; Chang, G; Gordon, S; Lin, H (2008)
The EGF-TM7 receptors, a subfamily of adhesion-GPCRs mostly restricted to leukocytes, are known to express multiple functional protein isoforms through extensive alternative cis-splicing. Here, we demonstrate that EGF-TM7 pre-mRNAs also undergo the rare trans-splicing, leading to the generation of functional chimeric receptors. RT-PCR and in silico analyses of EMR2 transcripts identified unique fragments containing the EGF-like motif 3 of a closely related EGF-TM7 gene, CD97, in addition to the alternative cis-spliced products. The sequence swapping is restricted to the EGF-3 exon, generating unique EMR2(1-2-3*-5) and EMR2(1-2-3*-4-5) molecules, which are functional in ligand-binding as the wild-type EMR2(1-2-3-4-5) and CD97(1-2-3-4-5) receptors. Our results suggest that human leukocytes employ trans-splicing as well as cis-splicing to increase the repertoire of functional adhesion-GPCRs.